Pengaruh Strategi Pembelajaran Relating, Experiencing, Applying, Cooperating, Transfering (REACT) terhadap Kemampuan Koneksi Matematika Siswa Kelas X SMAN 2 Ranah Batahan Kabupaten Pasaman Barat - Nadison, Alfin; Fitri, Haida; Aniswita, Aniswita; Risnawita, Risnawita (MASALIQ, 2025)
This research is an experimental study which aimss to see whther theree is a significant infIuence of the learning strategy relating, exsperiencig, appliying, cooperating, transferring (REACT) on the mathematical connection abilities of class X students at SMAN 2 Ranah Batahan, West Pasaman Regency. The population in this study were all class X students of SMAN2 Ranah Batahan. The samples in this study were two local areas, namely experimental class X.3 and control class X.2, totaIing 59 students. The sampling technikue was carried out using random sampling. The Instrument used is a mathematical connection ability test. Next, tests were carried out on both sample classes. Before testing, pre-requisite tests were carried out, namely the normality test and homogeneiti test. This research obtained hipothesis test results using the t-test, namely t_hitung=2.064, and t_hitung> t_((0.95;57)),so that it accepted H_1and rejected〖 H〗_0. So, the mathematical connection abilities of students who take part in learning using the REACT learning strategy are beter than student who takes part in learning using exspository learning strategies.